Assessment of Some Selected Pesticide Residues and Associated Soils from Six Farming Communities of Girei Local Government Area, Adamawa State, Nigeria - Reuben, Usaku; Hope, Emmanuel; Farimani, Dowell B. (Kwaghe International Journal of Sciences and Technology, 2025)
This study assessed the concentrations of pesticide residues in leguminous crops and associated soils from six farming communities in Girei Local Government Area, Adamawa State, Nigeria. Sampling was conducted in Tashan Turmi, Wuro Dole, Madugu, Sebere, Bakalci, and Jabi Lamba. Standard analytical procedures were used, with pesticide residue analysis performed using a Gas Chromatograph-Mass Spectrometer (GC-MS), Agilent Technologies GC 7890B, MSD 5977A. In legume samples, detected pesticide residues included atrazine (0.93 µg·kg⁻¹), 2,4-D (0.275 µg·kg⁻¹), cypermethrin (0.066 µg·kg⁻¹), and fenitrothion (0.051 µg·kg⁻¹), all of which were below Codex Maximum Residue Limits (MRLs). In soil samples, higher concentrations were observed, with 2,4-D at 86.361 µg·kg⁻¹, dimethoate at 1.009 µg·kg⁻¹, alachlor at 3.382 µg·kg⁻¹, and atrazine at 0.857 µg·kg⁻¹. These results indicate moderate environmental contamination due to agrochemical usage, reflecting anthropogenic influence in the agricultural practices of the region. The study underscores the need for regular pesticide monitoring, the adoption of safer agricultural practices, and increased public awareness to ensure food safety and safeguard environmental health.